Assessing the effect of domestic resource mobilization on Namibia's economic development - Ambunda, Katrina Kandiwapa (Graduate School of Business (GSB), 2024)
Effective resource mobilization from both domestic and foreign sources is necessary to achieve economic growth. However, the decline in trade and financial flows brought on by the 2009 global financial crisis, together with the unpredictability and volatility of development assistance flows globally, increased the need for more stable and long-term development funding alternatives. Thus, domestic resource mobilization (DRM) has emerged as a crucial instrument for achieving and sustaining rapid growth in developing countries. Since DRM can expand the available budgetary space, encourage quicker economic growth, and lessen poverty. As such, the aim of this study was to empirically measure the impact domestic resource mobilization strategies have had on Namibia's Economic growth in the period 1990 to 2020. The study evaluated and investigated the causal relationship between DRM and economic growth in Namibia using the Harrod and Domar growth model. On specified growth models, the study applied the ARDL Bounds testing approach to cointegration. The study discovered strong evidence for a connection between Namibia's DRM and economic growth. Thus, the study finds with a 98 percent confidence that there would be a long term, positive causal relationship between tax revenue, domestic savings, and domestic credit. Inferring that domestic savings, taxation, and credit patterns can have a direct and beneficial impact on the pace of growth of the Namibian economy over time. Additionally, the study concludes that government actions through banking sector policies and strategies can have a significant and long-lasting impact on Namibia's economic growth. Therefore, the study recommends that the Namibian government to initiate policies that trigger more savings, and support technology enhancement towards curtailing the economy's capital output ratio.